2016
DOI: 10.1002/jcp.25613
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein Kinase G and Reactive Oxygen Species in the Regulation of Podocyte Function in Health and Disease

Abstract: Podocytes and their foot processes form an important cellular layer of the glomerular barrier involved in the regulation of glomerular permeability. Disturbing the function of podocytes plays a central role in the development of proteinuria in diabetic nephropathy. Retraction of the podocyte foot processes that form slit diaphragms is a common feature of proteinuria; although, the correlation between these events in not well understood. Notably, it is unclear whether podocyte foot processes are able to regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 78 publications
(117 reference statements)
0
8
0
Order By: Relevance
“…Podocytes form an important cellular layer of the glomerular filtration barrier, which is involved in the regulation of glomerular permselectivity [34]. Podocyte injury or dysfunction plays a pivotal role in the development of proteinuria in all forms of glomerular nephritis and DN [35, 36]. Hence, maintaining the structural and functional integrity of podocytes and protecting podocytes from injury have become potential therapeutic approaches for CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Podocytes form an important cellular layer of the glomerular filtration barrier, which is involved in the regulation of glomerular permselectivity [34]. Podocyte injury or dysfunction plays a pivotal role in the development of proteinuria in all forms of glomerular nephritis and DN [35, 36]. Hence, maintaining the structural and functional integrity of podocytes and protecting podocytes from injury have become potential therapeutic approaches for CKD.…”
Section: Discussionmentioning
confidence: 99%
“…13 Podocytes are especially vulnerable to oxidative stress, which often leads to their dysfunction and causes proteinuria. 14,15 For instance, knockout mice lacking extracellular superoxide dismutase, an antioxidant expressed at high levels in normal adult kidneys, are sensitized to various glomerular injury induced by doxorubicin, chronic angiotensin II infusion, or protein overload and experience more severe proteinuria compared with wild-type control subjects. 16 However, extracellular superoxide dismutase null mice exhibit no difference with wild-type control subjects in kidney injury after unilateral ureteral obstruction.…”
mentioning
confidence: 99%
“…Previous studies have reported that ROS may be upstream signals for activation of p38 MAPK [30][31][32]. Interestingly, ROS produced by NADPH oxidase may be fed back to the G protein itself, since ROS directly activate Gi and Go without activating receptors [25,33]. ROS leads to an increase in the binding form of Gαi-GTP, resulting in the release of Gβγ from Gi and Go, which can activate the phosphorylated P38 MAPK and phosphoinositol 3-OH kinase signaling pathway, leading to Akt dephosphoryla-tion [33].…”
Section: Discussionmentioning
confidence: 99%